Impact of endometriosis on women's life decisions and goal attainment: a cross-sectional survey of members of an online patient community. Issue 4 (27th April 2022) - Missmer, Stacey A; Tu, Frank; Soliman, Ahmed M; Chiuve, Stephanie; Cross, Sarah; Eichner, Samantha; Antunez Flores, Oscar; Horne, Andrew; Schneider, Beth; As-Sanie, Sawsan
Abstract : Objectives: To examine women's perceptions of endometriosis-associated disease burden and its impact on life decisions and goal attainment. Design: An anonymous online survey was distributed in October 2018 through the social media network MyEndometriosisTeam.com. Participants: Women aged 19 years and older living in several English-speaking countries who self-identified as having endometriosis. Outcome measures: Patients' perspectives on how endometriosis has affected their work, education, relationships, overall life decisions and attainment of goals. Subanalyses were performed for women who identified as 'less positive about the future' (LPAF) or had 'not reached their full potential' (NRFP) due to endometriosis. Results: 743 women completed the survey. Women reported high levels of pain when pain was at its worst (mean score, 8.9 on severity scale of 0 (no pain) to 10 (worst imaginable pain)) and most (56%, n=415) experienced pain daily. Women reported other negative experiences attributed to endometriosis, including emergency department visits (66%, n=485), multiple surgeries (55%, n=406) and prescription treatments for symptoms of endometriosis (72%, n=529). Women indicated that they believed endometriosis had a negative impact on their educational and professional achievements, social lives/relationships and overall physical health. Most women 'somewhat agreed'/'strongly agreed' that endometriosis caused them to lose time in life (81%, n=601), feel LPAF (80%, n=589) and feel they had NRFP (75%, n=556). Women who identified as LPAF or NRFP generally reported more negative experiences than those who were non-LPAF or non-NRFP. Conclusions: Women who completed this survey reported pain and negative experiences related to endometriosis that were perceived to negatively impact major life-course decisions and attainment of goals. Greater practitioner awareness of the impact that endometriosis has on a woman's life course and the importance of meaningful dialogue with patients may be important for improving long-term management of the disease and help identify women who are most vulnerable.